Uji Validitas dan Respon Siswa Pengembangan E-Modul Kimia Berbasis Science, Environment, Technology, Society (SETS) Terintegrasi Nilai-Nilai Keislaman Pada Materi Sistem Koloid - Zeni Aprilia, Lovty; Sri Wahyuni, Tutik (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
Teaching materials that can be used for self-study by students, stimulate students' thinking skills by associating chemical concepts with approaches to science, environment, technology, and society as well as containing the integration of Islamic values are needed so that students get a complete concept andit is hoped that students can apply the concept to the real situations. This research aims to develop e-module based Science, Environment, Technology, and Society (SETS) which is integrated with Islamic values in colloidal system material. This researchand development use 7 stages of the RnD model from Sugiyono, namely potential problems, information gathering, product design, design validation, design revision, product manufacture, and limited product trials. The research instruments were needs analysis questionnaires, validation sheets, and student response questionnaires. E-module that was developed was validated by three validators to measure its validity in terms of material, media, and the integration of Islamic values. Product revisions were carried out according to the suggestions of the validators, then limited tests to find out student responses to the e-module being developed. The results of the validation of material experts, media, and integration of Islamic values successively obtained an average percentage of 96.0%, 95.1%, and 85.0% with very valid categories. The results of student responses obtained an average percentage of 83.6% in the very good category.